Konsep Perlindungan Hukum Bagi Pengungsi Anak Dari Ukraina Dalam Perspektif Hukum Pengungsi Internasional - Rachma Rizky Melania Latuconsina; Arman Anwar; Dyah Ridhul Airin Daties (Balobe Law Journal, 2023)
Introduction: The war in Ukraine caused Ukrainian refugees, including children, to be forced to leave their homes to seek protection in areas that were still safe within the country of Ukraine as Internally Displaced Persons or IDPs.Purposes of the Research:  This study aims to find out how the concept of legal protection for children who become refugees as a result of armed conflict and how the implementation of legal protection for children who become internally displaced persons in Ukraine.Results of the Research: The concept of humanitarian intervention to protect child refugees is the responsibility of the state as the national authority of Ukraine. but the conditions of war make a country unable to carry out its responsibilities as well as possible to protect internally displaced children as victims of war in their country. Although without intending to ignore the rights of child refugees, a country in a war situation will certainly place more strategic interests on military defense as its top priority, rather than other affairs and interests. the lack of proper livelihood and education for child refugees in Ukraine is one of the proofs showing that the Ukrainian state has not been successful as the main responsibility for protecting child refugees in the country. Therefore, the main responsibility cannot only be placed solely on the national authorities of the Ukrainian state, but must be the responsibility of all nations in the name of humanity, as is the case with international refugees who receive international protection. Children are a vulnerable group, very different from adult refugees. They need special attention so that they require more or different protection and handling measures because of their age. The best principle for the child (best interest of the child) must be the basis of his protection.